Seasonal variations of performance parameters in female elite handball - Kolodziej, M.; Schmidt, M.; Jaitner, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: For elite handball players, a high level of physical fitness is of particular importance not only to improve performance but also to prevent injuries. Up to now, less empirical evidence is given how physical performance changes over season (Granados et al., 2008). Furthermore, changes of injury risk parameters haven`t been investigated yet. Especially for female athletes, injuries in lower extremities (e.g. ACL rupture) must be considered as a severe problem. For this reason, this study investigates changes in performance parameters and potential injury risk factors of the lower extremities of elite female handball players during the competition season. Methods: 16 elite female handball players of the first national league (mean age 25.8 +/- 3.6years) were tested at the end of the preparation (T1) and the first competition period (T2). The assessment included 20m sprint test, drop jump test (DJ), landing technique test (LESS), Functional Movement Screen (FMS) as well as lactate threshold test. Sprint times at 0-5m (t5) and 0-20m (t20), velocity (v) and heart rate (hf) at 4mmol bloo lactate threshold, contact time (ts) and reactive strength index (RSI) as well as LESS Score and FMS Score were determined. T-test (p 0.05 criterion) and Cohens d were calculated. Results: Sprint times for 5m (T1: 1.2 ± 0.1s; T2: 1.2 ± 0.1s) and 20m (T1: 3.4 ± 0.1s, T2: 3.4 ± 0.1s), FMS Score (T1: 17.3, T2: 17.5), hf (T1: 171, T2: 174bpm) and v (T1: 13.1m/s, T2: 13.2m/s) did not show any substantial differences for both measures. LESS Score decreased 14.5% (5.5 to 4.7) whereas RSI increased 4.8% (150 to 157). Both didn`t show any statistical significance. Only ts decreased significantly (p= 0.012; d=0.388) between T1 (194.4ms) and T2 (175.9ms). Discussion: Changes of ts and RSI indicate an increased reactive strength of the lower extremities, whereas - in accordance to Granados et al. (2008) - sprint and endurance parameters remained stable. These findings confirm that a specific level of physical performance acquired in the preparation period can be maintained and partly improved during the first competition period in elite female handball players. In addition, the risk of being injured did not rise as potential injury risk factors decreased tendencially. For deeper insight in the development of performance parameters and injury risk factors longitudinal studies are needed that also consider how training contents and loads correspond with performance and risk of injury.